Effect of partial substitution of iso-valent Mo at Cr-site on electronic structure and physical properties of Fe2CrAl. (June 2021) - Yadav, Kavita; Mukherjee, K.
Abstract: Heusler alloy Fe2 CrAl exhibits a ferromagnetic behaviour below Curie temperature ( T C ) ∼ 202 K along with presence of cluster glass (CG) phase near freezing temperature ( T f ) ∼ 3.9 K and Griffiths phase (GP) above 300 K. The physical properties of this alloy are very sensitive to substitutions and anti-site disorder. Here, we investigate the effect of partial substitution of Mo at Cr-site on physical properties of Fe2 CrAl. Structural and morphological analysis confirms the single phase cubic structure of the substituted alloys. Increment in Mo concentration shifts the T C towards lower temperature, which is ascribed to the effect of increased hybridization strength between 3 d -4 d states of Fe/Cr/Mo. Additionally, systematic analysis of AC susceptibility, magnetic memory effect and time dependent magnetization studies confirm the presence of CG-like phase near ( T f ) ∼ 3.5 K in Fe2 Cr0.95 Mo0.05 Al. Such feature gets suppressed towards lower temperature with an increase of Mo concentration, i.e. below 1.8 K in Fe2 Cr0.85 Mo0.15 Al. The origin of the glassy signature is ascribed to the decrement in magnetic anisotropy with Mo concentration. A partial increment in magnetic entropy change is also noted near T C with the increase in Mo substitution. Interestingly, at high temperatures (above 350 K), GP phase persists in both the alloys due to the presence of anti-site disorder. Highlights: Structural and physical properties of Fe2 Cr1-x Mox Al alloys are studied. Suppression of ferromagnetic ordering ( T C ) and cluster glass phase with Mo substitution at Cr site. Persistence of Griffiths phase above 300 K in both alloys. Partial increment in magnetic entropy change near T C with the increase in Mo concentration.